Polymorphisms of CYP17A1, CYP19, and androgen in Brazilian women with uterine leiomyomas - Rosa, Fabiola Encinas [UNESP]; Canevari, Renata de Azevedo; Ambrosio, Eliane Papa [UNESP]; Ramos Cirilo, Priscilla Daniele [UNESP]; Pontes, Anaglória [UNESP]; Rainho, Claudia Aparecida [UNESP]; Rogatto, Silvia Regina [UNESP] (Walter de Gruyter & Co, 2008)
Background: Uterine leiomyomas are common, benign, smooth muscle tumors representing a significant public health problem. The aim of this study was to investigate CYP17A1, CYP19, and androgen (AR) polymorphisms, their relative risks for uterine leiomyomas and possible associations with clinical parameters.Methods: Uterine leiomyoma tissues and blood samples were obtained from 87 patients, as were peripheral blood samples from 68 control women. Clinical data were recorded in both groups. The CYP17A1 (rs743572) polymorphism was analyzed by PCR-RFLP, and the CYP19 [TTTA](n) repeat and AR [CAG](n) repeat were analyzed using PCR-based GeneScan analysis. AR loss of heterozygosity (LOH) and microsatellite instability were also evaluated, while samples exhibiting LOH were analyzed for X inactivation.Results: Clinical parameters related to disease development did not differ between cases and controls. CYP17A1 *A2/*A2 genotype was prevalent in non-white women. CYP17A1, CYP19, and AR genotypes and alleles did not differ between groups. However, alleles presenting [TTTA](7) repeats in intron 4 of CYP19 were more frequent in the control group (p=0.0550). Shorter and longer [CAG]n repeat alleles of AR were exclusive to the leiomyoma group. The LOH assay showed allele losses at AR locus in four informative tumors and X chromosome inactivation analysis revealed that these tumors retained the active allele.Conclusions: The overall lack of association between uterine leiomyomas with polymorphisms involved in steroidogenesis or steroid metabolism is consistent with the hypothesis that these polymorphisms do not substantially contribute to the development of these tumors.
Keywords: androgen (AR); CYP17A1; CYP19; polymorphism; uterine leiomyoma